2017
DOI: 10.1509/jmr.15.0485
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Salespeople Quit? An Empirical Examination of Own and Peer Effects on Salesperson Turnover Behavior

Abstract: Salesperson turnover can have a negative overall effect on a firm. Research on salesperson turnover has conceptually studied the consequences of voluntary turnover on a firm. However, little empirical research has investigated the antecedents of salesperson turnover—specifically, the role of own effects (relative performance, customer satisfaction, and goal realization) and peer effects (peer performance variance and turnover). Therefore, the authors propose a framework to assess the influence of own factors (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(38 citation statements)
references
References 74 publications
1
33
0
Order By: Relevance
“…For example, the competitive nature of sales employees has been found to be correlated with perceptions of how competitive their peers are (Brown et al, 1998; Schrock et al, 2016). Similar peer influences have been found for a range of workplace outcomes and attitudes, including employee’s turnover intentions (Sunder et al, 2017), commitment to new strategies (Hayati et al, 2018), organizational identification (Kraus et al, 2012), and technology adoption (Weinstein & Mullins, 2012), among others. Though peer effects yield similar results to peer-learning approaches, they differ significantly in terms of how these effects are achieved.…”
Section: Introductionsupporting
confidence: 55%
“…For example, the competitive nature of sales employees has been found to be correlated with perceptions of how competitive their peers are (Brown et al, 1998; Schrock et al, 2016). Similar peer influences have been found for a range of workplace outcomes and attitudes, including employee’s turnover intentions (Sunder et al, 2017), commitment to new strategies (Hayati et al, 2018), organizational identification (Kraus et al, 2012), and technology adoption (Weinstein & Mullins, 2012), among others. Though peer effects yield similar results to peer-learning approaches, they differ significantly in terms of how these effects are achieved.…”
Section: Introductionsupporting
confidence: 55%
“…Transformative actions help enhance salespeople’s job satisfaction (Aydogmus et al, 2018), and such positive actions toward enhancing customer satisfaction have also been repeatedly shown to reduce turnover (e.g. Sunder et al, 2017), in a somewhat self-reinforcing cycle. A spiritual personal orientation also helps an employee finding meaning at work (Karakas, 2010), and an ability to engage in helping to institute change and contributing to a learning environment to help others makes changes as well (Howard, 2002).…”
Section: The Cross-cultural and Religiosity Modelmentioning
confidence: 99%
“…David, Avery, Witt, and McKay (2015) found that aggregate coworker turnover was positively related to a focal employee's (supervisor‐rated) likelihood of turnover. Likewise, in a sample of business‐to‐customer salespersons, Sunder, Kumar, Goreczny, and Maurer (2017) found that the proportion of workplace peers that voluntarily quit was positively related to the likelihood that one would quit. Furthermore, peer voluntary turnover increased the risk of turnover twice as much as peer involuntary turnover (increased risk of 2.88% as compared with 1.15%), suggesting that coworker voluntary turnover is more likely to translate into employee voluntary turnover.…”
Section: How Does Turnover Spread?mentioning
confidence: 99%
“…For example, turnover contagion may be more likely depending upon the time of year, the competitiveness of the labor market, the industry, or the type of work; identifying these trends will provide insights regarding when and how organizations may implement certain retention strategies. Moreover, the type of turnover (e.g., dismissal and downsizing) may be perceived by stayers differently and therefore has a different influence on their propensities to leave (Sunder et al, 2017). As such, practitioners may need to consider the organizational, professional, or industrial context before assuming that turnover contagion processes will generalize to their specific context.…”
Section: Future Research Directionsmentioning
confidence: 99%